2013
DOI: 10.1111/apt.12460
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: probiotics in the management of lower gastrointestinal symptoms in clinical practice - an evidence-based international guide

Abstract: BackgroundEvidence suggests that the gut microbiota play an important role in gastrointestinal problems.AimTo give clinicians a practical reference guide on the role of specified probiotics in managing particular lower gastrointestinal symptoms/problems by means of a systematic review-based consensus.MethodsSystematic literature searching identified randomised, placebo-controlled trials in adults; evidence for each symptom/problem was graded and statements developed (consensus process; 10-member panel). As res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
126
1
14

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(144 citation statements)
references
References 69 publications
3
126
1
14
Order By: Relevance
“…Wellcontrolled intervention trials, systematic reviews and metaanalyses provide convinc ing evidence of the benefits of probiotics, including ones with valuable public health implications. 68,72 Clarifying the proper scope and appropriate use of the term pro biotic is important so that all stakeholders in the probiotic field, as depicted in Figure 1, share an understanding of probiotics that is consistent with current research. This clarification will facilitate continued advances in probiotic research and will ensure probiotic benefits are properly communicated to consumers and patients.…”
Section: Discussionmentioning
confidence: 99%
“…Wellcontrolled intervention trials, systematic reviews and metaanalyses provide convinc ing evidence of the benefits of probiotics, including ones with valuable public health implications. 68,72 Clarifying the proper scope and appropriate use of the term pro biotic is important so that all stakeholders in the probiotic field, as depicted in Figure 1, share an understanding of probiotics that is consistent with current research. This clarification will facilitate continued advances in probiotic research and will ensure probiotic benefits are properly communicated to consumers and patients.…”
Section: Discussionmentioning
confidence: 99%
“…27 Over the years general assessments have remained rather similar, presuming an overall positive effect whilst claiming a lack of high-quality data: "Probiotics may improve symptoms of irritable bowel syndrome and can be used as supplement to standard therapy." 19 "While our analyses suggest that probiotic use may be associated with improvement in IBS symptoms compared to placebo, these results should be interpreted with caution given the methodological limitations of contributing studies.…”
Section: Introductionmentioning
confidence: 99%
“…68,69 A systematic review of 18 RCTs involving 1806 IBS patients and consensus voting reported a high grade of evidence for the effect of probiotics on abdominal pain, and a good consensus agreement. 57 The abdominal pain was significantly alleviated in 5 of the 6…”
Section: Global Efficacy Of Probiotics In Irritable Bowel Syndrome: Dmentioning
confidence: 98%